AMPLIFIKASI PCR DOMAIN D1/D2 28S rDNA MENGGUNAKAN PRIMER ITS1 DAN ITS4 SAMPEL DNA DARI Candida tropicalis YANG DIISOLASI DENGAN METODE PENDINGINAN - Hermansyah Hermansyah; Novian Sutami; Miksusanti Miksusanti (Tanjungpura University, 2018)
The purpose of this research was to isolated DNA from the yeast C. tropicalis with freeze thawing method -200 C conducted on 3 colonies of C. tropicalis. Each colony threated variations of cooling, 3x15 minutes, 3x25 minutes and 3x35 minutes, to break the cell walls. Subsequently all the samples amplified with 3 variations of PCR cycles, 15 cycles, 25 cycles and 35 cycles, after all of the samples isolated by freeze thawing method -200 C. Its was known that sample A15 has the smallest concentration of DNA yeast C. tropicalis, ie 50 µg/mL, while sample C35 had the largest concentration of DNA yeast C. tropicalis, ie 225 µg/mL. The result of the research indicated that the best condition can be reached in 3x35 minutes. On 35th cycle has clearer C. tropicalis DNA bands than the 25th and 15th PCR cycle. C. tropicalis DNA bands at 35th cycles there were 7 DNA bands were detected and bright bands on a long 35 minutes cooling. In the 25th and the 15th cycle, there was no DNA bands were detected in all samples. Based on the results obtained, the amplification process must be carried out at least 35 times cycles so that the C. tropicalis DNA bands can be detected.